Mortgage Lending to Individuals in Russia during the Financial Crisis - Alexandrova, L.S.; Zakharova, O.V.; Matveevskii, S.S. (Journal of Reviews on Global Economics, 2018)
In this paper, the authors gave an overview of the main models of mortgage lending, and presented the results of their comparative analysis. The experience of mortgage lending in developed countries during the financial crisis of 2008 is considered. It is noted that a two-level model of mortgage lending in Russia is currently used, which allows the state to control the mortgage lending market, to realize refinancing of commercial banks issuing mortgage loans using securitization. The authors considered mortgage lending in Russia during the financial crises of 2008 and 2014, and its qualitative analysis was carried out. The results of the analysis allowed the authors to conclude that the state, represented by the Agency for Housing Mortgage Lending (AHML), played a crucial role in supporting mortgage lending in Russia during financial crises. It is shown that the government subsidized the interest rate on mortgage lending, which allowed not only to stabilize its volumes after the financial crisis of 2014, but also to ensure growth. The authors used the regression model for analyzing the statistical data of mortgage lending, which made it possible to identify factors that significantly influenced the volume of mortgage lending in Russia in the period under review. The results of the study have been summarized, specific recommendations aimed at further development of mortgage lending in Russia have been prepared.